Estimating Combining Ability of Yield and its Components in Upland Cotton Through Line ´ Tester Analysis: Line and Tester Crosses Analysis for Cotton - Baloch, Muhammad Jurial; Solangi, Jameel Ahmed; Jatoi, Wajid Ali; Rind, Imdad Hussain; Veesar, Nasreen Fatima (Biological Sciences - PJSIR, 2014)